The level of compliance of type II diabetes mellitus patients in controlling blood sugar - Nabilla Suratman; Liasari Armijn; Amran Nur (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
Diabetes mellitus is a chronic disease in the form of a metabolic disorder characterised by increased blood sugar levels that exceed normal limits. The purpose of the study was to determine the characteristics of type DM patients based on their level of adherence to drug use. The study used analytical descriptive methods with a cross-sectional study approach. Research samples were determined using the accidental sampling method on subjects who encountered as many as 44 pieces that doctors have diagnosed in the Kalumata Health Centre work area and according to inclusion criteria. Variable measurement using the Morisky Medication Adherence Scale questionnaire and validity and reliability analysis using SPSS version 25. Further tests were performed using bivariate Pearson correlation analysis. The results of the statistical analysis obtained sig values. (2-tailed) between age and gender, BPJS users' compliance rates are 0.510, 0.109, and -0.192, respectively. This means that there is no correlation or relationship. The variables of education level and type of work are 0.005 and 0.014, which significantly influence the level of compliance. It can be concluded that the variables that substantially impact the level of adherence of type 2 DM patients are education level and type of work. It is essential to constantly monitor and evaluate the effectiveness of implementing these recommendations to ensure an increase in the compliance rate of type 2 DM patients.